2005
DOI: 10.1128/aem.71.4.1865-1869.2005
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Effects on Biocontrol of Penicillium roqueforti by Pichia anomala J121 during Airtight Storage of Wheat

Abstract: The biocontrol yeast Pichia anomala inhibits the growth of a variety of mold species. We examined the mechanism underlying the inhibition of the grain spoilage mold Penicillium roqueforti by the biocontrol yeast P. anomala J121 during airtight storage. The biocontrol effect in a model grain silo with moist wheat (water activity of 0.96) was enhanced when complex medium, maltose, or glucose was added. Supplementation with additional nitrogen or vitamin sources did not affect the biocontrol activity of the yeast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
75
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 31 publications
0
75
0
1
Order By: Relevance
“…Beyond economic losses, the growth of fungi in foods causes a decrease of the nutritional value and the synthesis of allergenic spores and hazardous mycotoxins (23). Traditionally, fungicides and chemical preservatives have been used to prevent fungal growth, but concerns about environmental pollution and consumer health, along with problems of microbial resistance, favor the demand for alternative methods of control (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond economic losses, the growth of fungi in foods causes a decrease of the nutritional value and the synthesis of allergenic spores and hazardous mycotoxins (23). Traditionally, fungicides and chemical preservatives have been used to prevent fungal growth, but concerns about environmental pollution and consumer health, along with problems of microbial resistance, favor the demand for alternative methods of control (16).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, P. anomala (Wickerhamomyces anomalus, according to the latest taxonomic system) was shown to inhibit the growth of fungi in airtight-stored cereal grains (32). The biocontrol effect in a model grain silo with moist wheat (water activity of 0.96) was attributed to the antifungal action of metabolites derived from glycolysis rather than to competition for nutrients or activity of cell wall lytic enzymes (16).…”
mentioning
confidence: 99%
“…With respect to the substantial inhibition of P. agglomerans and E. coli in our earlier study, where the moisture content of the grain was only 18% (14), it seems unlikely that killer proteins are the sole mechanism, if they play any role at all. It has been suggested that the volatile ester ethyl acetate is involved in antimold activity (6,8). An antibacterial activity of ethyl acetate has been shown (2), but to our knowledge, no further studies are available.…”
mentioning
confidence: 93%
“…Traditionally, chemical preservatives and fungicides are used to inhibit fungal growth but concerns about environmental pollution and consumer health, along with problems of microbial resistance, favour the demand for alternative methods in controlling the growth of fungi (Druvefors et al, 2005). The shelf life of bread has been reported to be extended when certain LAB strains were added to bread formulations (Muhialdin et al, 2011a;Ogunbanwo et al, 2008;Rizzello et al, 2010;Ryan et al, 2011) (Table 2).…”
Section: Shelf Lifementioning
confidence: 99%